Equal pay in the North Yorkshire School Meals Service, 1995 (1995)
1995 1960-2000 "Equal pay in the North Yorkshire School Meals Service, 1995" [EP0216], 1995 This photograph shows Dorothy Ratcliffe and Susan Crosby celebrating their equal pay victory outside the House of Lords. Mrs Ratcliffe and the other claimants in this case worked for North Yorkshire County Council as catering assistants, serving meals in various schools. The school catering service had to be put out to compulsory competitive tender under the Local Government Act 1988. The Council decided that it had to reduce its labour costs if its in-house school catering tender was going to succeed against private sector catering companies. The Council therefore cut the women's basic pay and other benefits leaving them on worse terms and conditions than several groups of male Council employees whose work had been rated as equivalent to theirs under the Council's job evaluation scheme. The women claimed equal terms with those men. The House of Lords ruling in their favour resulted in some £2 million back pay for the women involved and the re-grading of their posts.